The role of thermal cycling on twinning in metastable beta-Ti alloy. (15th April 2022) - Sun, Bin; Sun, Kuishan; Meng, Xianglong; Wang, Jun
Abstract: Twinning in a Ti−26Nb alloy during thermal cycling was investigated by transmission electron microscopy. The interrelationships between displacive transformation and twinning were proposed. Fine 112 β 1 ¯ 1 ¯ 1 β twins and preferentially formed ω particles were observed in the β matrix after 100 cycles. The 112 β 1 ¯ 1 ¯ 1 β twins nucleated in ω particles and grew by merging twin embryos. Upon further increasing the cycle number to 500, 332 β 11 3 ¯ β twins bounded with laminated α" martensite were observed instead. The interfacial twin boundary α" phase mediated the martensitic transformation of the adjacent region, leading to the formation of 332 β 11 3 ¯ β twins. Graphical abstract: Image, graphical abstract